2001
DOI: 10.1103/physrevlett.87.067007
|View full text |Cite
|
Sign up to set email alerts
|

Do Superconductors Have Zero Resistance in a Magnetic Field?

Abstract: We show that dc voltage versus current measurements of a YBa(2)Cu(3)O(7-delta) film in a magnetic field can be collapsed onto scaling functions proposed by Fisher et al. [Phys. Rev. B 43, 130 (1991)] as is widely reported in the literature. We find, however, that good data collapse is achieved for a wide range of critical exponents and temperatures. These results strongly suggest that agreement with scaling alone does not prove the existence of a phase transition. We propose a criterion to determine if the dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…Gauge glass models for the VG transition do not show a finite T transition in three dimensions, once effects of screening are included [71]. Also, recent work questions earlier reports supporting a scaling description of the experimental data on disordered cuprates [72,73]. Theoretically, the evidence appears to favour a low-temperature glassy phase without long-ranged phase correlations, at least in the weak disorder limit [11].…”
Section: Universal Phase Diagram For Disordered Type-ii Supercondmentioning
confidence: 60%
“…Gauge glass models for the VG transition do not show a finite T transition in three dimensions, once effects of screening are included [71]. Also, recent work questions earlier reports supporting a scaling description of the experimental data on disordered cuprates [72,73]. Theoretically, the evidence appears to favour a low-temperature glassy phase without long-ranged phase correlations, at least in the weak disorder limit [11].…”
Section: Universal Phase Diagram For Disordered Type-ii Supercondmentioning
confidence: 60%
“…Although Strachan et al 15 suggested that agreement with scaling alone does not prove the existence of a phase transition, but experimental evidence for the vortex-glass phase has been obtained for various high-T c superconductors such as Y-123, [10][11][12] Tl-2212, 13,14 MgB 2 , 16 and Ba 0.55 K 0.45 Fe 2 As 2 (Ref. 17) through the scaling exponent, as predicted by vortex-glass and modified vortex-glass theory.…”
Section: -13mentioning
confidence: 98%
“…In the following we use scaling arguments to show that this is actually a BKTlike transition and to obtain the critical exponent z and the transition temperature. The transition temperature is obtained from the derivative plot as suggested by Strachan et al 19,20 The proposed criterion for I-V data is that log V vs log I isotherms above and below T BKT must have opposite concavities at the same applied currents. Figure 1(b) shows the current dependence of the derivative of the log V vs log I isotherms of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the resistance data drops abruptly below 87 K suggesting a true superconducting state in our pure 2D system below 86 K. It is interesting to remark that the same set of parameters z , b, and T BKT consistently accounted for the resistance measurements and for the scaling, which is not necessarily the case if the opposite concavity criterion by Strachan et al is not observed. 19,20 Due to the large scaling flexibility equally satisfactory scaling plots can be constructed for different sets of b , z, and T BKT . In fact, if we tentatively fix the value of z = 2 for conserving the concept of universality of the BKT, it is actually possible to scale the data of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation